Gap Junction Channelopathies and Calmodulinopathies. Do Disease-Causing Calmodulin Mutants Affect Direct Cell–Cell Communication? - Camillo Peracchia (International Journal of Molecular Sciences, 2021)
The cloning of connexins cDNA opened the way to the field of gap junction channelopathies. Thus far, at least 35 genetic diseases, resulting from mutations of 11 different connexin genes, are known to cause numerous structural and functional defects in the central and peripheral nervous system as well as in the heart, skin, eyes, teeth, ears, bone, hair, nails and lymphatic system. While all of these diseases are due to connexin mutations, minimal attention has been paid to the potential diseases of cell–cell communication caused by mutations of Cx-associated molecules. An important Cx accessory protein is calmodulin (CaM), which is the major regulator of gap junction channel gating and a molecule relevant to gap junction formation. Recently, diseases caused by CaM mutations (calmodulinopathies) have been identified, but thus far calmodulinopathy studies have not considered the potential effect of CaM mutations on gap junction function. The major goal of this review is to raise awareness on the likely role of CaM mutations in defects of gap junction mediated cell communication. Our studies have demonstrated that certain CaM mutants affect gap junction channel gating or expression, so it would not be surprising to learn that CaM mutations known to cause diseases also affect cell communication mediated by gap junction channels.